GRAS-1 is a novel regulator of early meiotic chromosome dynamics in C. elegans. - Marina Martinez-Garcia; Pedro Robles Naharro; Marnie W Skinner; Kerstin A Baran; Laura I Lascarez-Lagunas; Saravanapriah Nadarajan; Nara Shin; Carlos G Silva-García; Takamune T Saito; Sara Beese-Sims; Brianna N Diaz-Pacheco; Elizaveta Berson; et al. (PLoS Genetics, 2023)
Chromosome movements and licensing of synapsis must be tightly regulated during early meiosis to ensure accurate chromosome segregation and avoid aneuploidy, although how these steps are coordinated is not fully understood. Here we show that GRAS-1, the worm homolog of mammalian GRASP/Tamalin and CYTIP, coordinates early meiotic events with cytoskeletal forces outside the nucleus. GRAS-1 localizes close to the nuclear envelope (NE) in early prophase I and interacts with NE and cytoskeleton proteins. Delayed homologous chromosome pairing, synaptonemal complex (SC) assembly, and DNA double-strand break repair progression are partially rescued by the expression of human CYTIP in gras-1 mutants, supporting functional conservation. However, Tamalin, Cytip double knockout mice do not exhibit obvious fertility or meiotic defects, suggesting evolutionary differences between mammals. gras-1 mutants show accelerated chromosome movement during early prophase I, implicating GRAS-1 in regulating chromosome dynamics. GRAS-1-mediated regulation of chromosome movement is DHC-1-dependent, placing it acting within the LINC-controlled pathway, and depends on GRAS-1 phosphorylation at a C-terminal S/T cluster. We propose that GRAS-1 coordinates the early steps of homology search and licensing of SC assembly by regulating the pace of chromosome movement in early prophase I.